Challenging the status quo: a scoping review of value-based care models in cardiology and electrophysiology - Osoro, Lucia; Zylla, Maura Magdalena; Braunschweig, Frieder; Leyva, Francisco; Figueras, Josep; Pürerfellner, Helmut; Merino, Josè Luis; Casado-Arroyo, Ruben; Boriani, Giuseppe (Europace, 2024)
The accomplishment of value-based healthcare (VBHC) models could save up to
Online verfügbar: 19. August 2024, Artikelversion: 12. September 2024
Gesehen am 07.03.2025